2023
DOI: 10.3390/pharmaceutics15030900
|View full text |Cite
|
Sign up to set email alerts
|

Micro-Injection Moulding of PEO/PCL Blend–Based Matrices for Extended Oral Delivery of Fenbendazole

Abstract: Fenbendazole (FBZ) is a broad-spectrum anthelmintic administered orally to ruminants; nevertheless, its poor water solubility has been the main limitation to reaching satisfactory and sustained levels at the site of the target parasites. Hence, the exploitation of hot-melt extrusion (HME) and micro-injection moulding (µIM) for the manufacturing of extended-release tablets of plasticised solid dispersions of poly(ethylene oxide) (PEO)/polycaprolactone (PCL) and FBZ was investigated due to their unique suitabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 61 publications
(104 reference statements)
0
2
0
Order By: Relevance
“…As shown in Figure 3A, the decomposition temperature of PP separators is around 400 °C. Although the decomposition temperature of coated separators is slightly decreased to 377 °C because of the lower decomposition temperature of polymer coatings [39,40] , they are still enough for battery application. As shown in Figure 3B, the PP-PEO 60w (EO:Li + = 8:1) and PP-blended PEO 60w /PCL 5w separators show improved thermal stability compared to the commercial PP separator.…”
Section: Physical Property Characterization Of Separatorsmentioning
confidence: 99%
“…As shown in Figure 3A, the decomposition temperature of PP separators is around 400 °C. Although the decomposition temperature of coated separators is slightly decreased to 377 °C because of the lower decomposition temperature of polymer coatings [39,40] , they are still enough for battery application. As shown in Figure 3B, the PP-PEO 60w (EO:Li + = 8:1) and PP-blended PEO 60w /PCL 5w separators show improved thermal stability compared to the commercial PP separator.…”
Section: Physical Property Characterization Of Separatorsmentioning
confidence: 99%
“…Indeed, it was proposed for the fabrication of controlled-release DDSs to be orally administered, even resorting to novel manufacturing approaches (e.g. injection molding, 3D printing, electrospinning) [24,25,27,[92][93][94][95].…”
Section: Manufacturingmentioning
confidence: 99%
“…Fenbendazole loaded with Mobil composition of matter number 41 showed enhanced delivery capability to PC-3 cells [14], the micelles containing fenbendazole and rapamycin (1:2 ratio) prepared via freeze-drying showed slower release in vitro [15], fenbendazole-encapsulated poly-(D,L-lactide-co-glycolide) acid nanoparticles prepared by an oil-in-water emulsion method [16] could increase water solubility, enhance absorption, and exert significant anti-cancer effects in EOC cells and xenograft models including PDX [17], fenbendazole dispersed in PEO/PCL blendbased matrices prepared by hot-melt extrusion revealed that PCL retarded the drug release proportionally to the content of such polymer incorporated [18]. Compatibility between fenbendazole and three polymeric excipients was evaluated [19], and tablets of plasticized solid dispersions of poly-(ethylene oxide)/polycaprolactone and fenbendazole improved the drug solubility and release [20]. These research works did not make significant solubility improvement and could not reach the requirements for a cancer therapeutic dose (5-10 mg/mL), therefore, more effects need to be put to find new formulation with significant water solubility increasing [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%